(untitled) (Jurnal Bahasa, 2005)
Throughout the development of linguistics from its beginning until to-day, there are generally two main aspects that are given emphasis by linguists. The first aspect deals with theoretical and conceptual is-sues, whereas the second focuses on the application of linguistic theo-ries to various sub-disciplines of linguistics, such as dialectology, pho-netics and phonology, semantics, pragmatics, grammar, discourse analysis and several others. Without any intention to downgrade or lessen the importance of attention given to the application of theories, propose that the theoretical and conceptual aspect ought to be given more serious attention and greater effort, especially because some problems and issues emerging in the application of theories are based on theoretical and conceptual issues. This paper discusses one of the fundamental theoretical and conceptual aspects of knowledge, includ-ing linguistics, that is epistemology. The discussion also covers the nature and reality of language, the role and contribution of language in the development of human’s concept of "self" and its realization and issues related to the development of linguistics in the Malay world.